THE OUTCOME OF SARS-COV2 INFECTION AMONG CHILDREN WITH CANCER IN SULAIMANIYAH PROVINCE, IRAQ - Abdulla, Khanda Muhammed; Salih, Khalid Hama; Rashid, Bakir Rahim (Journal of Sulaimani Medical College, 2023)
Background The most significant and pervasive health issue faced the globe during the last 2years was coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV2). Patients diagnosed with childhood cancer may have impaired immune systems due to their illness or therapy, increasing their vulnerability to COVID-19 infection. Objectives To determine the outcome of COVID-19 in children with malignancy who received chemotherapy, explain characteristic features, and assess the severity of COVID-19 among haematological vs oncological malignancies Patients and Methods This Retro-prospective cohort study was carried out in the Hiwa oncology Hospital in the Sulaimaniyah governorate from November 2021 to February 2022 on 70 children with cancer using PCR to confirm their COVID-19 infection (60 haematological cases and ten oncological cases). Results Among the total 70 patients involved in the study, 52.9% were males, 47.1% were females, and their mean age was 8.83 ± 4.3. About sixty-two (90%) cases had haematological malignancies, and 8(10%) had oncological malignancies. The most predominant symptom was fever (82.9%), followed by cough (67.1%). On the other hand, 58 (82.9%) cases had mild disease, and 8 (11.4%) had the moderate disease. Chest x-ray infiltration was found in 12 (17.1%) cases; 14 (20.0%) children needed hospital admission, only 1 (1.4%) case required intensive care unit (ICU) admission, and 6 (8.6%) patients needed O2 therapy. Sixty-seven children recovered from COVID-19, and three children died. Conclusion Most children with cancer (CwC) had mild infections and were outpatients with benign outcomes. Haematological malignancies, especially acute lymphoblastic leukaemia (ALL), are the commonest malignancies among COVID-19 patients. Most COVID-19 patients were symptomatic, with fever and cough being the predominant symptoms.
Keywords: Children; COVID-19; SARS-CoV 2; Malignancy; Hiwa Hospital